2021
DOI: 10.1097/nnd.0000000000000755
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Nursing Education for Thermoregulation

Abstract: Neonatal nurses provide essential care in the hospital setting for improving infants' morbidity and mortality outcomes by preventing hypothermia after delivery. This quality improvement project describes the development and implementation of a web-based educational activity, demonstrating that online education effectively increases nurse knowledge and commitment to thermoregulation practices. A learning management system provides nursing professional development practitioners an effective method of improving n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…The results also supported a previous review that reported high satisfaction scores toward web applications among nursing students and health personnel as they were easier to concentrate on than offline education or traditional face‐to‐face training (Kong, Kim, & Kim, 2021; Widiasih et al, 2022). The web application is an innovative media that helps learners understand the content easily, is convenient for learning anytime and anywhere, provides immediate feedback, and motivates them to learn by using attractive animation and videos (Bond et al, 2018; Du et al, 2013; Gest, 2021; Koch et al, 2010; Kong, Kim, & Kim, 2021; Park et al, 2020; Wang et al, 2016; Widiasih et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results also supported a previous review that reported high satisfaction scores toward web applications among nursing students and health personnel as they were easier to concentrate on than offline education or traditional face‐to‐face training (Kong, Kim, & Kim, 2021; Widiasih et al, 2022). The web application is an innovative media that helps learners understand the content easily, is convenient for learning anytime and anywhere, provides immediate feedback, and motivates them to learn by using attractive animation and videos (Bond et al, 2018; Du et al, 2013; Gest, 2021; Koch et al, 2010; Kong, Kim, & Kim, 2021; Park et al, 2020; Wang et al, 2016; Widiasih et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Today, web applications are widely used for health professional education. Health personnel are satisfied using these as they enable learning to be completed conveniently to the user, offer improved access, and increase knowledge and practices among health personnel (Bond et al, 2018; Gest, 2021; Kim & Hwang, 2022; Kong, Kim, & Kim, 2021; Park et al, 2020; Wang et al, 2016; Widiasih et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Despite calls for demonstration of the value NPD practice brings to healthcare organizations (Harper & Maloney, 2022), evidence of NPD contributions to positive outcomes in children's hospitals is scarce. Although evidence is found of the value of staff education in the literature, in most cases, these data arise from quality improvement projects, both with NPD participation (Benning & Webb, 2019; Hammontree & Kinderknecht, 2022) and without NPD participation (Gavriloff, 2012; Gest, 2021; Kisting et al, 2019; Longo et al, 2008), along with academic research (Cantrell et al, 2005; Cantrell & Brown, 2006; Lutfi et al, 2019; Mariana et al, 2019; Mustafa et al, 2021). A single systematic review was found.…”
Section: Review Of Literaturementioning
confidence: 99%